THE INFLUENCE OF PROFITABILITY, LIQUIDITY AND CAPITAL STRUCTURE ON COMPANY VALUE WITH CORPORATE SOCIAL RESPONCIBILITY AS MODERATING VARIABLES - Lefrando Agustinus Saragih; Regina Tota Angelina Sigiro; Renni Veronika Marpaung; Riska Monalisa Sitompul; Adam Afiezan (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Background: The higher this ratio, the more efficient the company in using the company's current assets to meet its current liabilities, so as to minimize the company's failure to meet its short-term obligations to creditors. If the company wants to maintain its business continuity, it must have the ability to pay off all its financial obligations when they fall due. This ratio is used to measure how liquid a company is. Method : The research method is an activity that uses a systematic method to obtain data which includes data collection. Result : Based on the results of the residual test, the coefficient value on the Firm Value variable is -0.052 with a significance value of MRA 3 respectively. each of 0.987 is greater than 0.05. Conclusion : Profitability partially has a significant effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the 2017–2020 period. High profitability will give a positive signal to investors that the company produces in favorable conditions. This attracts investors to own company shares.